CHANGING TRENDS IN DIAGNOSTIC CRITERIA OF DIABETES MELLITUS: AN OVERVIEW - RAKHEE YADAV; S.K.VERMA; J.P.BHARTIYA; M.K.NANDKEOLIAR (International Journal of Pharma and Bio Sciences, 2013)
Over the years, the matter of classification and diagnostic criteria of Diabetes mellitus have lacked consensus among health care professionals. Healthcare providers have got their own perceptions based on the knowledge acquired during their study period, training and practical exposure. However, with the increasing knowledge in the field of etiopathogenesis and the treatment of Diabetes; it is deemed essential in the healthcare community to remain comprehensively acquainted with the new developments and changing trends in this field. Since the diagnostic criteria are changing from time to time, it is imperative to update the knowledge of these trends.